(untitled) (Research, Society and Development, 2021)
The main goal of this study was to investigate if there is an association between Oral Herpes (OH) recurrent episodes and Single Nucleotide Polymorphisms (SNPs) in IL1A, IL10, and IL1RN genes in a group of Brazilian Para-athletes. This transversal study was prepared according to the STrengthening the REporting of Genetic Association Studies (STREGA) guidelines. Oral examination and DNA collection for genotyping were performed in a non-probabilistic convenience sampling composed of Brazilian para-athletes who participated in a Brazilian selective competition. Data referring to the general characterization of sample were collected through a self-reported questionnaire. Candidate genes were chosen with the UCSC Genome Browser and SNPs in IL1A gene (rs17561, rs1304037), IL10 gene (rs1800871), and IL1RN gene (rs9005) were selected and investigated in allelic, genotypic, dominant, and recessive models. Hardy-Weinberg equilibrium was evaluated in each SNP. The sample was composed of 273 para-athletes (63 (23.4%) practice swimming, 61 (22.3%) powerlifting and 145 (63.7%) athletics). OH recurrent episodes was related by 47 (17.2%) para-athletes and the presence of T allele in the rs1304037 increased chance of OH. These findings suggest that rs1304037 in IL1A gene is associated with OH recurrent episodes in para-athletes.